2020
DOI: 10.1007/s12144-020-01142-z
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive model of disordered eating among aesthetic athletic girls: Exploring the role of body image-related cognitive fusion and perfectionistic self- presentation

Abstract: The incidence of disordered eating among athlete populations is considerably higher than in the general population. Less well understood is the body image-related emotional processes that might lead to disordered eating attitudes and behaviours, specifically among aesthetic athletic girls. Thus, the aim of the present study was to explore the role that body image-related cognitive fusion plays in disordered eating, and the mediating role of body image-related perfectionist self-presentation on this relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Participants who had negative beliefs about their physical characteristics were more likely to report higher levels of cognitive fusion.The findings from this study support previous literature establishing a relationship between cognitive fusion and physical characteristics (e.g., Paixão et al, 2020;Trindade et al, 2018;Trindade & Ferreira, 2015), although most of the literature in this area is focused on body dissatisfaction and disordered eating. Cognitive fusion and experiential avoidance mediated the relationship between how one evaluated their body and their maladaptive coping strategies (Zucchelli et al, 2020).…”
Section: Negative Beliefs About Physical Self and Fused Thoughtssupporting
confidence: 88%
See 1 more Smart Citation
“…Participants who had negative beliefs about their physical characteristics were more likely to report higher levels of cognitive fusion.The findings from this study support previous literature establishing a relationship between cognitive fusion and physical characteristics (e.g., Paixão et al, 2020;Trindade et al, 2018;Trindade & Ferreira, 2015), although most of the literature in this area is focused on body dissatisfaction and disordered eating. Cognitive fusion and experiential avoidance mediated the relationship between how one evaluated their body and their maladaptive coping strategies (Zucchelli et al, 2020).…”
Section: Negative Beliefs About Physical Self and Fused Thoughtssupporting
confidence: 88%
“…We predicted that those who engage in experiential avoidance might also be more likely to discriminate against others in their own group. Cognitive fusion has been identified as a factor contributing to body evaluation (Zucchelli et al, 2020), perfectionistic self-presentation (Paixão et al, 2020), and body dissatisfaction (Trindade et al, 2018). Therefore, it was expected that those with higher levels of cognitive fusion would also report higher levels of dissatisfaction with traditional Filipinx physical characteristics.…”
Section: Colonial Mentality and The Filipinx American Experiencementioning
confidence: 99%
“…We differentiated between team and individual sports based on the varying roles of cooperation, competition, and bonding among participants in these two categories of sport (Landkammer et al, 2019). Besides whether or not they could be classified as team or individual sports, we grouped martial arts (Gubbels et al, 2016; Harwood et al, 2017) and aesthetic sports (Krentz & Warschburger, 2011; Paixão et al, 2021) into separate categories based on the emphasis on Asian traditions, on the one hand, and physical appearance and “showcase,” on the other hand. We believed these characteristics were more important than their “team” or “individual” nature to explain their potential differential associations with children’s psychosocial adjustment.…”
Section: Longitudinal Links Between Organized Sports and Psychosocial...mentioning
confidence: 99%
“…During competition, the technical quality of movements is evaluated by judges, as is the creativity of the routines. Given this notion of performance and “showcase” the aesthetic sports subculture tends to emphasize physical appearance and thinness, even among children (Krentz & Warschburger, 2011; Paixão et al, 2021). Davison et al (2002) found that girls aged 5–7 years participating in aesthetic sports reported higher levels of weight-related concerns than those in nonaesthetic or no sports.…”
Section: Longitudinal Links Between Organized Sports and Psychosocial...mentioning
confidence: 99%
“… 23 Perfectionistic self-presentation targets three interpersonal facets: (a) perfectionistic self-promotion (ie, an excessive need to appear as being perfect to others, unrealistic self-presentation of one’s perfection), (b) non-display of imperfection (ie, fear/need to avoid showing imperfection or shortcomings to others or making errors in public by avoiding situations or hiding mistakes) and (c) non-disclosure of imperfection (ie, the need to avoid telling others/admitting shortcomings and evasiveness in interactions with others). 23 Paixão et al 24 found, for example, a significant and positive relationship between body-image-related perfectionistic self-presentation, body mass index, disordered eating and age among young female aesthetic athletes. In addition, perfectionistic self-presentation was found to mediate the relationship between body-image-related cognitive fusion and disordered eating.…”
Section: Introductionmentioning
confidence: 99%